PELAYANAN DAN KEPUASAN PELANGGAN UED-SP PADA BUMDES LALA SENTOSA DI DESA PERKEBUNAN SUNGAI LALA, INDRAGIRI HULU, RIAU - Akbari, M. Rizki Fadilah; Elida, Septina; Hamidi, Wahyu; Fahrial, Fahrial (Jurnal Daya Saing, 2025)
Customer satisfaction is the main target to be able to survive in the midst of fierce competition This research aims to analyze customer satisfaction with the services provided by UED-SP BUMDes Lala Sentosa in Perkebunan Sungai Lala Village. A sample of 100 customers was selected using simple random sampling. Data analysis employed Service Quality (Servqual), Important Performance Analysis (IPA), and the Customer Satisfaction Index (CSI). The results indicate that customers are still less satisfied with the services at UED-SP BUMDes Lala Sentosa. Therefore, performance improvement is necessary. The top priority attributes located in Quadrant I are: Availability of computers and telephones as supporting technology, BUMDes office work schedule (opening and closing hours), Friendliness of the management in serving customers. Furthermore, attributes in Quadrant II include: Strategic location of the BUMDes office, Honesty of UED-SP BUMDes management, Guarantee of easy loan requirements, and Patience of the management towards customers.